2010
DOI: 10.1002/app.32344
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of poly(urethane acrylate) films for ultraviolet‐curable coatings

Abstract: Four different UV-curable poly(urethane acrylate)s were prepared through the reaction of two diisocyanates [i.e., toluene-2,4-diisocyanate (TDI) and isophorone diisocyanate (IPDI)] and two polyols [i.e., polycaprolactone triol (PCLT) and polycaprolactone diol (PCLD)], and they were characterized with Fourier transform infrared spectroscopy. The mechanical properties, thermal properties, and water sorption of the cured poly (urethane acrylate)s were also investigated with respect to the chemical structures of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…These observations suggested that urethane acrylate prepolymer had been completely converted to PUA. These IR absorption bands of PUA were in corresponding with the spectra reported by Wang et al [], Çanak and Serhatli [], and Seo et al []. The chemical structure of PUA after UV curing is presented in Scheme .…”
Section: Resultssupporting
confidence: 79%
“…These observations suggested that urethane acrylate prepolymer had been completely converted to PUA. These IR absorption bands of PUA were in corresponding with the spectra reported by Wang et al [], Çanak and Serhatli [], and Seo et al []. The chemical structure of PUA after UV curing is presented in Scheme .…”
Section: Resultssupporting
confidence: 79%
“…The low degradation temperature, especially for the HEA-IPDI-HEA, was mainly attributed to fewer stable urethane groups existing in the aliphatic polyurethane acrylates, which could decompose to form alcohol and isocyanate groups. The results obtained here agree with the literature [26,27]. Additionally, with the introduction of additional multi-functional modified CNT and GO, more bifunctional HEA-IPDI-HEA was injected, which led to a decrease in the thermal stability.…”
Section: Synthesis and Preparationsupporting
confidence: 90%
“…These results indicate that all of the samples in our system presented excellent adhesive performance on the PC substrate and that the limited increase (from 1B to F) of the surface hardness did not lead to the complete hardening of the coating film, which often leads to a decrease in the adhesive performance. The abrasive test is an accurate and repeatable way to determine the abrasion wear characteristics of inks and coatings [27]. The RCA abrasion test presents the combined properties of surface hardness, rigidity and adhesion of the surface coating and is typically used in the 3C (Computer, Communication and Consumer Electronics) industry to the test surface for resistance to abrasion and wear.…”
Section: 3mentioning
confidence: 99%
“…It can be seen that a mass loss began at 130 • C for the F4 membrane, due to the partial removal of the alkyl carbonate solution and some solvent remaining. Generally, the first decomposition stage of PUA results from the degradation of urethane segments and the subsequent stage is due to the degradation of soft segments from the polyether or polyester (Gite et al, 2010;Seo et al, 2010). Hence, it is assumed that the second massloss peak corresponds to the urethane bond breakage, which occurs at between 250 • C and 360 • C in this UVcured polymer electrolyte blend.…”
Section: Thermal Analysismentioning
confidence: 99%